2014
DOI: 10.15406/apar.2014.01.00006
|View full text |Cite
|
Sign up to set email alerts
|

A Future Perspective in Crop Protection: Chitosan and its Oligosaccharides

Abstract: Studies on the biological activities of chitosan and its oligomers have been increasing, as no single type of chitosan or its oligomers exerts all of the above bioactivities. Moreover, different chitosan derivatives and enzymatic products have different structures and physicochemical properties, which may result in novel bioactivities or novel findings in known bioactive compounds. Chitosan oligosaccharides also have been shown to induce various plant defense-related cellular responses and possess by themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 61 publications
3
23
0
6
Order By: Relevance
“…It has been reported that chitosan has been widely used as a potential alternative to in-feed antibiotics in piglets and broiler chickens due to many beneficial biological properties of it, such as promoting the growth performance [ 6 , 7 ], anti-oxidative [ 8 ] and immunity modulation [ 9 ]. However, chitosan is restricted to be used in food and biomedical applications because of its difficult solubility and instability [ 10 ]. Low-molecular-weight chitosan (LC, < 150 kDa) and chito-oligosaccharide (COS, < 5 kDa) are obtained from chitosan by physical, chemical or enzymatic methods, and have much higher solubility and stability than chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chitosan has been widely used as a potential alternative to in-feed antibiotics in piglets and broiler chickens due to many beneficial biological properties of it, such as promoting the growth performance [ 6 , 7 ], anti-oxidative [ 8 ] and immunity modulation [ 9 ]. However, chitosan is restricted to be used in food and biomedical applications because of its difficult solubility and instability [ 10 ]. Low-molecular-weight chitosan (LC, < 150 kDa) and chito-oligosaccharide (COS, < 5 kDa) are obtained from chitosan by physical, chemical or enzymatic methods, and have much higher solubility and stability than chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…По нашему мнению, обнаруженная у образца Витаплан, КЖ + коллоидный хитин более высокая способность индуцировать устойчивость пшеницы к темно-бурой пятнистости и бурой ржавчине по сравнению с исходным, обусловлена хитоолигосахаридами, образующимися при гидролизе коллоидного хитина хитиназами бактерии (San-Lang et al, 2006). Известно, что хитоолигосахариды являются эффективными элиситорами индуцированной устойчивости в растениях (Yin et al, 2013;Deepmala et al, 2014). В результате их взаимодействия с рецепторами происходит активация комплекса защитных реакций неспецифического иммунитета растений.…”
Section: результатыunclassified
“…С другой стороны, известно, что хитин, хитозан и их олигомеры считаются мощными элиситорами иммунитета растений (Yin et al,2013;Deepmala et al,2014). Эти природные полисахариды в последнее время активно используются для улучшения биологической активности биопрепаратов, так как предполагается, что хитин и хитозан могут индуцировать (отдельно или в комбинации с бактериальными клетками) системную устойчивость к фитопатогенам.…”
unclassified
“…Chitosan (poly (1,4)-2-amino-deoxy-β-D glucose) is the deacetylated product of chitin which is commonly found in crustacean shells. It is a simple linear polysaccharide that constitutes the β-1-4 linked D-11 glucosamine (GlcN) and N-acetyl-D-glucosamine (GlcNAc) (Katiyar, Hemantaranjan, Singh, & Bhanu, 2014). Chitosan is known to induce plant growths (Dzung, Khanh, & Dzung, 2011), contain antifungal (Atai, Atai, Amini, & Salehi, 2017;Dananjaya et al, 2017) and antibacterial properties (Cui, Bai, Rashed, & Lin, 2018;D'Almeida et al, 2017).…”
Section: Introductionmentioning
confidence: 99%